NILAI TUKAR RUPIAH DAN NET EKSPOR INDONESIA 2000 – 2017 (GRANGER CAUSALITY TEST) - Try Beta Anggraini; Yefriza Yefriza (Convergence: The Journal of Economic Development, 2019)
The aims of this research is to find out the relationship of rupiah exchange rate and net export Indonesia. This research covers the periode for 2000.Q1-2017.Q4, used secondary data which were analyzed using Granger Causality Test and Augmented Dickey Fuller (ADF) and existing data processed by using computer program of Eviews 9.0. The stationary properties of the time series data are examined by using Augmented Dickey-Fuller (ADF) test. Granger Causality test is applied to find out long-run relationship along with causality among the variables. The result of the data analysis show that there is no causality between rupiah exchange rate and net xport. Granger Causality test showed that there is unidirectional causality between net export to rupiah exchange rate. It is mean that net export  effect rupiah exchange rate, but rupiah exchange rate does not effect net export. Keywords: Causality, Net Export, Exchange Rate